Determination of organic acids in avocado fermented juice by high performance liquid chromatography - Pichai Liawruangrath (2018)
© 2015 Chiang Mai University. All rights reserved. Avocado fermented juice was prepared. The organic acids: malic acid, citric acid and tartaric acid in this juice were determined by reversed phase high performance liquid chromatography. Ten microlitres of sample were taken for analysis of the three organic acids when the samples were stored at room temperature to ferment for 1, 2, 3 , 4, 5 weeks, 2 months and 8 months respectively. The chromatographic conditions for the optimal separation of malic, citric and tartaric acids on a LiChrosorb RP-18 column 5 μm, 4.6 × 250 mm at 210 nm were investigated. The optimized RP-HPLC method (mobile phase: MeOH: H2O (5:95 v/v) adjust pH of 2.5 using hydrochloric acid, flow rate 1.0 mL min-1) was validated. Calibration curves were linear for all the three acids over concentration ranges tested with r2 values of better than 0.999. The percentage recovery was found to be in the range of 99.7-106.0 with the % RSD of 1.02 - 1.13. The proposed method was applied to the determination of three organic acids in fermented juice. The maximum amounts of malic acid and tartaric acid followed by reasonable amount of citric acid were obtained at the first week of fermentation. The results compared flavorably with the published capillary zone electrophoresis method.The finding results suggest that the avocado fermented juice can be used as health supplement and also can be used in cosmetic products.